Ranking Meets Distance Education: Defining Relevant Criteria and Indicators for Online Universities - Pozzi, Francesca; Manganello, Flavio; Passarelli, Marcello; Persico, Donatella; Brasher, Andrew; Holmes, Wayne; Whitelock, Denise; Sangrà, Albert (International Review of Research in Open and Distributed Learning, 2019)
University ranking systems are being implemented with the aim of assessing and comparing higher education institutions at a global level. Despite their being increasingly used, rankings are often strongly criticized for their social and economic implications, as well as for limitations in their technical implementation. One of these limitations is that they do not consider the specific characteristics of online education. This study used a participatory approach to define a set of criteria and indicators suitable to reflect the specific nature of distance education. This endeavour will help evaluate and rank online higher education institutions more appropriately than in current practice, where indicators are devised for traditional universities. To this end, several stakeholders and informants were involved in a Delphi study in an attempt to reach the broader higher education institutions (HEI) community. According to the study participants, apart from students’ achievements and general quantitative measures of HEI performance, which are quite common in traditional ranking systems, teaching and student learning experience turned out to be the most important criteria. Student support, teacher support, technological infrastructure, research and organization were deemed middle ground criteria, while sustainability and reputation were regarded as the least important criteria.